Exploring the Strategies of Male Sterility for Hybrid Development in Hexaploid Wheat: Prevailing Methods and Potential Approaches - Muhammad Abdullah; Usama Sheraz; Arisha Tul Ain; Bisma Nasir; Sardar Hammad; Sajid Shokat (Rice)
Abstract Hybrid breeding has emerged as a pivotal strategy to enhance wheat crop yield, a critical step to meet the escalating food demand for the growing global population. Heterosis in wheat can boost crop yield; however, harnessing heterosis in bread wheat is complex and hindered by the species' inherent tendency for self-pollination, high genome ploidy, and limitation of male sterile lines. In contrast, the availability of genetic male sterility, and altering reproductive biology such as anther extrusion and floret opening, is challenging but could facilitate outcrossing. Despite the advancements in sterility systems and molecular tools, an efficient and environmentally stable wheat hybrid production system is still lacking. In this review, we examine the advantages and limitations of different male sterility sources utilized to date including, chemical hybridizing agents (CHAs), cytoplasmic male sterility (CMS), nuclear genic male sterility (NGMS), and environmental-sensitive male sterility (ESMS). Furthermore, we explore the potential of molecular tools such as marker-assisted selection (MAS), genome editing, and other genetic engineering approaches to accelerate hybrid wheat breeding efforts. Future research directions are proposed to develop robust, cost-effective systems by integrating conventional and molecular approaches with advanced screening methods including cytogenomics and next generation sequencing (NGS), which can reliably help to produce stable, high-yielding, and resilient hybrid wheat cultivars compared to current open-pollinated varieties. Collectively, these efforts are vital to achieve the food demands for escalating population under climate change scenario.